Pengaruh Pendidikan Kesehatan Dengan Media Poster Terhadap Pengetahuan Tentang Pencegahan Penyakit Hipertensi Pada Lansia Di Kampung Merapit Desa Waliwis - Nikhlah; Puspita Sari, Rina Puspita Sari; Pratiwi, Ayu (Gayaku Publisher, 2025)
The prevalence of hypertension is increasing, particularly among the elderly, making it a major health concern that requires serious attention. WHO in 2023 reported that 33% of the global population suffers from hypertension, while in Indonesia the prevalence is 29.2%. In Banten Province, more than 2.3 million cases were recorded, with Tangerang Regency as the highest contributor. A preliminary survey in Kampung Merapit, Waliwis Village, revealed that most elderly lacked knowledge of hypertension prevention; therefore, a simple and easily understood educational intervention is needed, such as poster media. This study aimed to determine the effect of health education using poster media on elderly knowledge of hypertension prevention. A quantitative method with a quasi-experimental one group pretest-posttest design was applied, involving 84 elderly selected through purposive sampling. The instrument was a knowledge questionnaire on hypertension, and data were analyzed using the Wilcoxon test. Results showed that before the intervention, 66.7% had poor knowledge and 33.3% moderate, whereas after the intervention all respondents (100%) had good knowledge. The Wilcoxon test showed p < 0.001, indicating a significant effect. Conclusion: poster-based health education effectively improves elderly knowledge regarding hypertension prevention.